2012
DOI: 10.1182/blood-2012-02-412296
|View full text |Cite
|
Sign up to set email alerts
|

The clinical implication of SRSF2 mutation in patients with myelodysplastic syndrome and its stability during disease evolution

Abstract: Recurrent somatic mutation of SRSF2, one of the RNA splicing machinery genes, has been identified in a substantial proportion of patients with myelodysplastic syndrome (MDS). However, the clinical and biologic characteristics of MDS with this mutation remain to be addressed. In this study, 34 (14.6%) of the 233 MDS patients were found to have SRSF2 mutation. SRSF2 mutation was closely associated with male sex (P ‫؍‬ .001) and older age (P < .001). It occurred concurrently with at least 1 additional mutation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
116
4
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 38 publications
11
116
4
1
Order By: Relevance
“…In the report by Qian et al [25], MDS patients with U2AF1 mutation also seemed younger than patients without this mutation, but the difference was not statistically significant. In our prior report, SRSF2 mutation, another spliceosome machinery gene mutation, occurred dominantly in older patients and was associated with male gender and mutations of RUNX1, IDH2, and ASXL1 [17]. Our data indicate that there are distinct clinical and genetic characteristics in MDS with different gene mutations even though the mutations involve the same mRNA-splicing machinery.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In the report by Qian et al [25], MDS patients with U2AF1 mutation also seemed younger than patients without this mutation, but the difference was not statistically significant. In our prior report, SRSF2 mutation, another spliceosome machinery gene mutation, occurred dominantly in older patients and was associated with male gender and mutations of RUNX1, IDH2, and ASXL1 [17]. Our data indicate that there are distinct clinical and genetic characteristics in MDS with different gene mutations even though the mutations involve the same mRNA-splicing machinery.…”
Section: Discussionmentioning
confidence: 84%
“…These findings suggest that U2AF1 mutation may play a role in the development, but not progression, of MDS. Our prior study showed that SRSF2 mutation was also stable during the disease evolution [17]. These findings suggest that the spliceosome gene mutations, at least SRSF2 and U2AF1 mutations, are more likely a primary hit in MDS development rather than a secondary hit that leads to disease progression.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…28 SRSF2 mutations has been described in 47% of chronic myelomonocytic leukemia 29 and, although less frequently, in other types of myelodysplastic and myeloproliferative neoplasms. [30][31][32] All neutrophilic post-polycythemic myelofibrosis cases showed only wild-type alleles for these genes, a finding that suggests that the neutrophilic proliferation arising during the fibrotic stages of polycythemia vera is caused by mechanisms biologically distinct from those involved in chronic neutrophilic leukemia or atypical chronic myeloid leukemia.…”
Section: Modern Pathology (2015) 28 1448-1457mentioning
confidence: 95%
“…SRSF2 mutations are seen in patients with MDS, CMML, MPN/PMF, and acute myeloid leukemia (AML) [12,13,16,[18][19][20], and are very rare in juvenile myelomonocytic leukemia [19,21]. In MDS and PMF, SRSF2 mutations are relatively common ( 15-20%) and are associated with shortened OS and LFS [16,18,22]. In CMML, SRSF2 is the most commonly mutated spliceosome gene (28-47%) and has been associated with older age, less pronounced anemia and a diploid karyotype [13,14,19,20].…”
Section: Introductionmentioning
confidence: 99%